Smoking increases transcription of human endogenous retroviruses in a newly established in vitro cell model and in normal urothelium - Gabriel, Ute; Steidler, Annette; Trojan, Lutz; Michel, Maurice Stephan; Seifarth, Wolfgang; Fabarius, Alice (Aids research and human retroviruses, 2010)
Human endogenous retroviruses (HERVs) accounting for 9% of the human genome are considered as surrogate markers for genetic instability and as a driving force of genetic variation. Moreover, they modulate regular gene activities and give rise to expression of disease-associated peptides that may serve as diagnostic markers or even targets for T cell-based immune responses. To date, no data are available on the potential link between urothelial carcinogenesis, HERV activity, and tobacco smoking, the main risk for bladder cancer. Here, we report on potential alterations in HERV transcription induced by smoking in a newly established in vitro model and in human urothelium. Normal human dermal fibroblasts were cultivated with urine from never (n = 6) and current smokers (n = 6) and transcription levels for the HERV subfamilies HERV-E 4-1, HERV-T S71-TK1, and HERV-K HML-6 were measured by quantitative real-time PCR. Tendencies toward increased mean transcript levels were detected for cells treated with urine from current smokers. Equally, activity measured in human urothelium supported an increase of HERV transcription in current smokers (n = 9) compared to never smokers (n = 4).
Gesehen am 20.11.2023